The study of transparent conducting gallium doped ZnO thin films in order to use in solar cells - Mahmoudzadeh Pirvahshi, Mojtaba (International Journal of Physical Research, 2018)
In this study, transparent conducting Ga-doped ZnO thin films were deposited on glass substrate using chemical spray pyrolysis technique. The effect of Ga-doping concentration (0, 1, 2 and 3 at.%) on microstructural, optical and electrical characteristics of layers have been investigated. The studies of X-ray diffraction and optical transmission spectra show these films have a hexagonal wurtzite structure with (002) preferred growth direction, also a high transmission of 85-95% in visible range. Data analysis show that the band gap energies in these films are varying in the range of 3.27-3.33 eV, consistent with the Burstein-Moss shift effect, with Urbach tail widths between 114-160 meV. The 2 wt% Ga sample showed the maximum figure of merit (3×10-2Ω-1), with an electron concentration and sheet resistance of ~1.42×1019 cm-3 and 13 kΩ/square, respectively.